Study of the proportion between women and men's balls of handball and the measurement of the hand of women and men handball players - Oliver Coronado, J. F.; Sosa Gonzalez, P. I. (EHF Scientific Conference 18.-19.11.2011, Wien, Österreich, 2011)
The aim of the present study is to know the relation between the measures of handball players´s hands and the measures of the balls in Under 14, Under 16 and Under18 age categories, women and men. Depending on the results, we will propose to the IHF to revise and modify the rule of ball´s measures, men and women in each sport category, to be in accordance with the anthropometric characteristics of the hand of the players.